2013
DOI: 10.3390/ijms140714171
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor Roles of miR-433 and miR-127 in Gastric Cancer

Abstract: The discovery of microRNAs (miRNAs) provides a new and powerful tool for studying the mechanism, diagnosis and treatment of human cancers. Currently, the methylation epigenetic silencing of miRNAs with tumor suppressor features by CpG island hypermethylation is emerging as a common hallmark of different tumors. Here we showed that miR-433 and miR-127 were significantly down-regulated in gastric cancer (GC) tissues compared with the adjacent normal regions in 86 paired samples. Moreover, the lower level of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 29 publications
8
75
1
Order By: Relevance
“…miR-433 has been demonstrated to be downregulated in several types of cancer tissue, including (10,(12)(13)(14)16). Consistent with this, the results of the present study also demonstrated the downregulation of miR-433 in breast cancer tissues, which suggests that miR-433 may be tumor-suppressive in breast cancer tissues.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…miR-433 has been demonstrated to be downregulated in several types of cancer tissue, including (10,(12)(13)(14)16). Consistent with this, the results of the present study also demonstrated the downregulation of miR-433 in breast cancer tissues, which suggests that miR-433 may be tumor-suppressive in breast cancer tissues.…”
Section: Discussionsupporting
confidence: 80%
“…However, caution must be exercised as miR-433 may have downstream targets other than AKT3. Previous studies have found that miR-433 targets Notch1, CREB1, PAX6, HDAC6, KRAS and c-Met in other types of cancer (10,12,13,16). Therefore, future studies must assess other targets of miR-433 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data, along with an analysis of a published dataset (27), showed that miR-433 was overexpressed in osteosarcoma tissues and cell lines. In combi nation with previous reports revealing the roles of miR-433 in various other types of cancer, including ovarian and gastric cancer (28,29), the present study further confirmed that miR-433 functions as an oncomiR in osteosarcoma. Furthermore, overexpression of miR-433 was shown to decrease the apoptosis of osteosarcoma cells by targeting PDCD4 in vitro.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the overexpression of miR-433 in a gastric cancer cell line suppressed cell growth and invasion by downregulating KRAS expression (8). Overexpression of miR-433 downregulated thymidylate synthetase mRNA and protein expression and enhanced the sensitivity of HeLa cells to 5-fluorouracil (9).…”
Section: Introductionmentioning
confidence: 99%